Laboratory evaluation of broflanilide (TENEBENAL™) against Anopheles gambiae in Moshi, Tanzania – delayed mortality, cross-resistance, and residual efficacy - Snetselaar, Janneke; Rowland, Mark W.; Azizi, Salum; Mawa, Benson; Malone, David J.; Kirby, Matthew J. (Frontiers in Tropical Diseases, 2023)
Introduction Broflanilide is a novel meta-diamide insecticide, which has a distinct mode of action compared to other active ingredients used for Indoor Residual Spraying (IRS). This study details a laboratory evaluation of broflanilide, of putative discriminating concentrations, potential cross-resistance, and residual efficacy on two substrates. Methods Mosquitoes were exposed to broflanilide in bottle bioassays to determine lethal concentrations (LC50 and LC95). These were used to calculate resistance ratios between the susceptible Kisumu and the pyrethroid-resistant Muleba-Kis strains of Anopheles gambiae s.s. Prototype wettable powder formulations of broflanilide were applied to mud and concrete to determine the optimal observation period for determining delayed mortality, and a Cox proportional hazards model was fitted to determine a potential dose response effect. Subsequently, residual efficacy of application rates ranging between 25 mg/m2 and 300 mg/m2 were monitored monthly. Results LC values of tested strains were not significantly different; therefore, the polyfactorial resistance mechanisms possessed by the resistant strain did not confer resistance to broflanilide. A significant effect of concentration and time since spraying was found on mosquito survival, indicating that higher broflanilide concentrations are more effective and that this effect was strongest immediately after spraying. Knockdown at 60min post exposure was negligible, with on average only 1% of all mosquitoes knocked down. On the mud surface, but not on concrete, there was a delayed killing effect, with mortality increasing until 72 hours after exposure. The residual efficacy test indicated that on concrete the 100 mg/m2 and 200 mg/m2 concentrations of both broflanilide 50WP formulations remained efficacious for 9 months post spraying. On mud, there were large variations in mosquito mortality from month to month. Generally, higher concentrations resulted in higher mortality, despite variation over time. Discussion Cross-resistance to broflanilide was not detected in mosquitoes with multiple resistance mechanisms. This opens up the possibility for wide-scale use of broflanilide, especially in areas with established pyrethroid resistance. Like some other insecticide classes, delayed mortality up to 72 hours post exposure was found for broflanilide. Promising residual efficacy was found with broflanilide 50WP formulations on concrete. On mud, efficacy varied and further testing with a refined formulation is recommended.